The Effectiveness of Position Arrangements on the Length of Recovery of Patients' Consciousness Level with General Anesthesia in the Recovery Room of RSUD Matraman - Teguh Dwi Kumbara; Arifah Rakhmawati (STIKep PPNI Jawa Barat, 2023)
Aims : This study aims to determine the effectiveness of semi-Fowler's and lateral positioning on the length of recovery of consciousness in patients with general anesthesia. Methods : A sample of 60 respondents was carried out using an independent T test with a significance of α = 0.05. If the test results in this study have an effect then it is obtained (ρvalue <0.05). Researchers will carry out the Normality Test and Homogeneity Test as a condition in the independent T test. Results : Researchers found that a patient's position changes how long it takes for them to wake up after surgery with general anesthesia by 87%. The largest number of respondents (35%) were between the ages of 36 and 40. This was followed by the age range of 26 to 30 years, with 16 respondents (26.7%), the age range of 20 to 25 years, with 13 respondents (21.6%), and the age range of 31 to 35 years, with at least 10 respondents (16.7%). Body temperature had a big effect on how long it took for people with general anesthesia to get better after surgery. The speed or length of a patient's return to awareness after surgery depends on the type of general anesthetic drug used. Studies show that the most widely used drug is propofol + ketamine + midazolam, followed by propofol + midazolam and fentanyl. Most of the time, a slow recovery is caused by leftover anesthetics, sedatives, or painkillers. A drug overdose can also make it take longer for a person to wake up. Conclusion : Researchers found that a patient's position and body temperature had a big effect on how long it took for them to wake up after surgery with general anesthesia. The most widely used drug is propofol + ketamine + midazolam, followed by propofol + midazolam and fentanyl. Slow recovery is caused by leftover anesthetics, sedatives, or painkillers.